Analysis of the Decision on the Settlement of Sharia Economic Bankruptcy Cases at the Central Jakarta Commercial Court - Ratnasari, Desi; Jayusman, Jayusman; Fauzi, Mohammad Yasir; Khoiruddin, Khoiruddin (ASAS, 2025)
Bankruptcy is a process in which a debtor who has financial difficulties to pay his debts is declared bankrupt by the court because the debtor cannot pay his debts, then the debtor's assets are distributed to creditors in accordance with the provisions. One of the sharia economic bankruptcy disputes resolved by the Commercial Court, which is under the District Court. One of them is the decision of the Central Jakarta Commercial Court Number 25/Pdt.Sus PAILIT/2020/PN.Niaga.Jkt.Pst. the focus of research in this article is how the judge's consideration in the Central Jakarta Commercial Court Decision Number 25/Pdt.Sus PAILIT/2020/PN.Niaga.Jkt.Pst and how is the analysis of sharia economic law on the judge's decision? The purpose of this study is to find out the judge's consideration in deciding bankruptcy case Number 25/Pdt.Sus-PAILIT/2020/PN.Niaga.Jkt.Pst and to find out the sharia economic law view of the judge's decision. The research approach used in this research is a normative approach, which focuses on the point of view of the provisions of Islamic law and positive law, both regarding legal aspects, legal principles or applicable legal theories. This research is descriptive analytic with library research method. The conclusion of this research resulted in two things. First, the legal considerations of the Panel of Judges rejected the application because it did not meet the bankruptcy requirements in accordance with the provisions of Article 2 paragraph (1) and Article 8 paragraph (4) of Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations (PKPU). Second, the Central Jakarta Commercial Court Decision Number 25/Pdt.Sus PAILIT/2020/PN.Niaga.Jkt.Pst is in accordance with the principles of sharia economic law through maqasid shari'ah.